Toxoplasma gondii Prevalence and Risk Factors among Female Students at Al-Yemenia University, Sana’a City, Yemen - Al-Wajeeh, Talal Saeed; Al-Hadheq, Ali Ahmed; Nomaan, Majeed Hazzaa; Edrees, Wadhah Hassan; Al-Shehari, Wadee Abdullah (Journal of Amran University, 2024)
Abstract Background: Toxoplasmosis is one of the most common human infections worldwide. It is caused by the intracellular protozoan Toxoplasma gondii. Therefore, this study aimed to determine the prevalence of Toxoplasma gondii infection among female students at Al-Yemenia University in Yemen. Methods: Two hundred female students were selected for this study and screened for Toxoplasma gondii antibodies using an immunochromatographic technique (ICT). Demographic, socioeconomic, risk factors, and behavioral data were collected using a pre-tested questionnaire via face-to-face interviews. Results: The seropositivity rate for T. gondii was (6.0%). The majority were from age groups of 18–20 and 21–24 years (41.7%), who lived in the urban area (83.3%), unmarried individuals (83.8%), and middle-income participants (66.7%), with a non-significant difference (P < 0.05). Female students who washed vegetables before eating had a high risk of T. gondii infection (OR = 4.810), followed by raising cats in the house (OR = 3.812), and had a history of blood transfusion (OR = 1.618). Conclusion: This study reported low seroprevalence among female students at Al-Yemenia University, Yemen. Environmental sanitation, personal hygiene, and health education are all required for promotion to prevent Toxoplasma gondii infection among female students.